Kinetic and thermodynamic studies of biomass pseudo-components under thermo-oxidative degradation conditions using asymmetric function of Bi-Gaussian as deconvolution technique. (April 2022) - Li, Weizhen; Huang, Yanqin; Liu, Huacai; Zhang, Yan; Jiang, Yang; Wang, Yan; Wan, Junfeng; Yin, Xiuli
Abstract: This work aimed at investigating the kinetic and thermodynamic characteristics of components of pine sawdust (PS), edible fungi spent substrate (FVSS) and their blend during thermo-oxidative degradation. The novelty focused on applying deconvolution technique to distinguish an overlapped peak into three individual peaks corresponding to pseudo-hemicellulose, pseudo-cellulose and pseudo-lignin, respectively. Particularly, the function of Bi-Gaussian was employed to capture the asymmetric reaction shapes. Mass loss was recorded using a thermal analyzer at heating rates of 10, 20 and 30 K min −1 in air atmosphere. Methods of Starink and master-plots were used for estimating kinetic triplet. The average activation energies of FVSS are lower than PS, with an order of pseudo-lignin > pseudo-hemicellulose > pseudo-cellulose corresponding to the ranges of 211.70–342.78, 139.00–172.53 and 128.08–146.99 kJ mol −1, respectively. The pre-exponential factor are all higher than E+10 s −1 demonstrating some simple complex chemical reactions occurred. Models of D2 and A1 dominate the degradation of pseudo-hemicellulose and pseudo-cellulose, respectively, in PS and the blend. The average values of Δ S, Δ H and Δ G are −51.62-146.31 J mol −1, 122.99–335 kJ mol −1 and 78 144.87–216.59 kJ mol −1, showing the non-spontaneous process and need energy to maintain. Graphical abstract: Image 1 Highlights: ∙ Deconvolution technique to solve kinetics of overlap peaks of biomass degradation. ∙ Bi-Gaussian was adopted to capture the asymmetric reaction shapes. ∙ E α 139–173, 128–147 and 212–343 kJ·mol-1 for hemicellulose, cellulose and lignin. ∙ Models of D2 and A1 dominate the degradation of hemicellulose and cellulose. ∙ Degradation process is non-spontaneous and endothermic.